Pengembangan E-Modul Biologi Berbasis Potensi Daerah Kerinci pada Materi Plantae dan Animalia : Development of Biological E-Modules Based on Kerinci Resources for Plantae And Animalia Materials - Miko Pratama; Asni Johari; Jefri Marzal (Universitas Jambi, 2018)
The lack of Biology teaching materials in senior high school in the Kerinci District has promoted this research. The purpose of this development research is to produce e-modules as teaching materials used by students in Biology subjects. The model used in developing this e-module is the 4-D model, which consists of 4 stages, namely defining, designing, developing, and disseminating. Biology e-modules on plantae and animalia material based on the potential of the Kerinci region were validated by media and material experts. The results of the media expert validation obtained the final percentage of 90% (very valid category) and the material expert validation obtained a percentage of 75% (valid category). From the results of the field test, the teacher responded that the e-modules produced were suitable for use in biology class X high school learning with a percentage of 92.5% (very good category). Furthermore, e-module trials on students obtained responses that the products produced were also proper to be used in biology learning in class X of senior high school. The small group test obtained a score of 85% (excellent category) and the large group test obtained score 78.3% (good category). The use of the developed e-modules in learning resulted in a score of 76.3% (successful category).